Legal Analysis of The Impact of Industrial Development on The Environment - Armansyah; Ujang Badru Jaman (The Easta Journal Law and Human Rights, 2023)
The environment is something that cannot be separated from human life. Because where someone lives, another environment is created and vice versa. The industry is a sectoral economy or activity that involves the processing of raw materials or the production of products, i.e., the use of skills and labor in the factory and the use of field tools to process the results on the ground and distribute them as the main work. Therefore, as an eye chain, the industry is also responsible for meeting land-related (economic) needs, i.e., agriculture, cultivation, and mining. To place the sector far from the country, the basis of economy, culture, and politics. Study law is carried out in a manner juridical normative is Conceptual research as what is written in regulation legislation or law conceptualized as a rule or the norm, which is benchmark behavior considered human deserves. Study law normative This is based on material primary and secondary laws, i.e., referring research to existing norms in regulation legislation. Development is a planned change process as one effort man in increasing the quality of his life. However, the development industry in Indonesia has a significant impact on the environment, resulting in pollution, damage to the climate forests, and depletion of source Power nature. The impact development industry on the environment in Indonesia has been attention for many years. This leads to an increased need for measures and legislation to reduce the negative impact of industrial development on the environment.